The Use of Digital Storytelling in Learning Spoken Narrative: A Case of a Private Vocational School in Jakarta - Sari, Ayu Nur Indah; Puspitaloka, Nina; Nugraha, Sidik Indra (Peneliti.net, 2024)
This study aimed to shed more light on the implementation of digital storytelling in learning spoken narrative and explore the students’ perception of learning spoken narrative through digital storytelling. The study employed a narrative inquiry approach and gathering the data through reflective journals and interviews. The research site is SMK Citra Mandiri Jakarta, with 6 participants consist of high, medium, and low achievements in English subject. The findings are thematically analyzed and categorized into one subtheme, which related to the research question. This study highlighted the implementation of DST was an effective strategy in narrative spoken that inserted digital medium such as laptop and projector. It helps students with vocabulary knowledge, easier to understood grammar and retelling the stories because the video contains a very interesting story, in the form of animation, with captions inserted, the characters are funny, creative and inspiring. However, this study also discussed that students had positive perceptions and there were no difficulties of using DST in learning speaking. This study concludes that DST is a strategy that can help students learn to spoke. Through this strategy, students could increase their vocabulary, grammar understanding, and spoken narrative in retelling. Thus, they could enjoy lessons in class more, so they felt happy and enthusiastic.